1989
DOI: 10.1164/ajrccm/139.6.1424
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Maximal Oxygen Uptake and Power during Cycle Ergometry in Subjects Older than 55 Years of Age

Abstract: One hundred twenty-eight healthy volunteers (81 women, 47 men) older than 55 yr of age were studied with an incremental progressive cycle ergometer test to a symptom-limited, maximal tolerable work load. Mean (+/- SD) age was 66 +/- 6 yr in women and 66 +/- 5 years in men. Subjects with a history of ischemic heart disease, diabetes, pulmonary disease, or neuromuscular disease were excluded. Smokers were included, but all subjects had normal FEV1 and FVC. The objective of the study was to compare measured value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 6 publications
0
46
1
2
Order By: Relevance
“…Relationships between VT and ventilation (V E) were examined, and a point of inflection was determined for each subject (22). We compared our measurements of peak V O2 with predicted normal values accounting for sex, age, height, and weight; a correction factor of 1.09 was applied to estimate the difference between predicted values obtained with cycle vs. treadmill ergometry since treadmill testing results in higher values for peak V O2 (6). Other exercise parameters were compared with the predicted normal values of Jones (27).…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between VT and ventilation (V E) were examined, and a point of inflection was determined for each subject (22). We compared our measurements of peak V O2 with predicted normal values accounting for sex, age, height, and weight; a correction factor of 1.09 was applied to estimate the difference between predicted values obtained with cycle vs. treadmill ergometry since treadmill testing results in higher values for peak V O2 (6). Other exercise parameters were compared with the predicted normal values of Jones (27).…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
“…V O2, oxygen uptake; V E, minute ventilation; MVC, maximal ventilatory capacity; RER, respiratory exchange ratio, V CO2, carbon dioxide output; VT, tidal volume; VC, vital capacity; ⌬IC, change in IC; F, breathing frequency; IRV, inspiratory reserve volume; TLC, total lung capacity; RER, respiratory exchange ratio; SpO2, oxygen saturation; PETCO 2 , partial pressure of end-tidal CO2; EELV, end-expiratory lung volume. *Predicted peak V O2 of Blackie et al (6) with 9% correction for treadmill from cycle values. †P Ͻ 0.05, significantly different within group.…”
Section: Physiological Responses To Exercisementioning
confidence: 99%
“…An initial analysis of available data on healthy subjects [1,2,12,118,[181][182][183][184][185][186][187][188][189][190][191] clearly indicated that only five of these studies [2,181,[184][185][186] fulfill minimum requirements to be considered as candidates to be used in the clinical setting [85]. However, Blackie et ah [184] cover a lim ited age span (55-80 yrs), and Bruce et al [186] pro vide data obtained with treadmill in a population of physically fit people. Hence, the analysis of potential studies in healthy sedentary people providing predic tion equations for peak V'02 obtained with incremental cycling exercise testing is reduced to three sets [12,181,185], Basic characteristics of these three studies are summ arized in table 7.…”
Section: Reference Valuesmentioning
confidence: 99%
“…Zusätzlich konnte der Sauerstoffpuls aus den Daten der maximalen Sauerstoffaufnahme, dividiert durch die maximale Herzfrequenz, annähend errechnet werden [4,9,10,16,20]. Bei Frauen zeigt sich eine gute Übereinstimmung mit sämtlichen Studien [4, 5, 7 -10, 13], siehe• " Abb.…”
Section: Der Maximale Sauerstoffpulsunclassified
“…Bei den Männern liegt der von Pothoff et al [5] und Herdy et al [13] für inaktive Männer bestimmte Sauerstoffpuls unterhalb der eigenen sowie der in den übrigen Studien [4,7,10,16] gefundenen Werte, vgl.…”
Section: Der Maximale Sauerstoffpulsunclassified